2022
DOI: 10.1016/j.mce.2022.111558
|View full text |Cite
|
Sign up to set email alerts
|

Selinexor improves the anti-cancer effect of tucidinostat on TP53 wild-type breast cancer

Abstract: Background: Histone deacetylase (HDAC) is closely related to the occurrence and development of breast cancer (BC). Its inhibitor (HDACi) has been used to treat BC, while the e cacy of clinical trials was not reached expectations. HDACi combined with other drugs may be an effective strategy. This study explored the effect of HDACitucidinostat combined with selinexor, anexportin 1 (XPO1) inhibitor, on BC cellsin vitro.Methods: BC cell lines of MCF-7 (wt-TP53), MDA-MB-175 (wt-TP53), MDA-MB-134 (mut-TP53), T47D (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…p53 is a carrier protein for XPO1 12,13 . Therefore, we conducted an immunofluorescence assay to clarify p53 status under KPT‐330 treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…p53 is a carrier protein for XPO1 12,13 . Therefore, we conducted an immunofluorescence assay to clarify p53 status under KPT‐330 treatment.…”
Section: Resultsmentioning
confidence: 99%
“…p53 is a carrier protein for XPO1. 12 , 13 Therefore, we conducted an immunofluorescence assay to clarify p53 status under KPT‐330 treatment. The results showed that XPO1 inhibition by KPT‐330 triggered the accumulation of p53 inside the nucleus (Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…Tucidinostat (chidamide), as a Class I HDAC inhibitor, has been shown to inhibit a variety of cancer growth [ 41 , 42 , 43 , 44 , 45 , 46 ]. Therefore, we selected Tucidinostat in our in vitro cell model to assess its effect on uLMS cell growth.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, combined treatment with MDM2 inhibitor, nutlin‐2, resulted in synergistic anti‐leukaemic effects in responsive blasts and cell lines 148 . Similarly, MDM2 inhibition enhanced Selinexor cytotoxicity in both neuroblastoma and ovarian cancer cell models and upregulated expression of p53 by HDAC inhibitor, tuconidostat, improved responsiveness of TNBC cell lines to Selinexor in a p53‐dependent manner 150–152 . Conflicting evidence implicating p53 as a predictor of Selinexor sensitivity suggests that differential in vitro and in vivo responsiveness is likely dependent on cancer subtype.…”
Section: Sine Resistancementioning
confidence: 99%